Molecular detection of hemoplasmas in rescued black-eared opossums (Didelphis aurita Wied-Neuwied, 1826) from southeastern Brazil, with evidence of a novel genotype infecting marsupials - de Oliveira, Ágatha Ferreira Xavier; Calchi, Ana Cláudia [UNESP]; Mongruel, Anna Claudia Baumel [UNESP]; Stocco, Anieli Vidal; Stocco, Naiara Vidal; Costa, Alexandre Carvalho; Mureb, Elizabeth Neves; Pires, Jeferson Rocha; Guimarães, Andresa; Balthazar, Daniel de Almeida; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP]; et al. (FapUNIFESP (SciELO), 2023)
There is a growing concern about the participation of wild hosts and reservoirs in the epidemiology of several pathogens, particularly within the context of environmental changes and the expansion of the One Health concept. The aim of this study was to investigate the presence of hemoplasmas in opossums rescued from the metropolitan region of Rio de Janeiro state, Brazil. Blood samples were collected from 15 Didelphis aurita and subjected to DNA extraction and PCR using primers for the 16S rRNA and 23S rRNA genes. Physical examination and hematological analysis were also performed. Three out of 15 opossums tested positive for hemotropic Mycoplasma spp. by PCR and showed hematological alterations such as anemia and leukocytosis. Clinical signs were non-specific and associated to traumatic lesions. The phylogenetic analysis indicated that the hemoplasma detected was positioned between ‘Ca. Mycoplasma haemodidelphis’ detected in D. virginiana from North American and hemoplasmas recently detected in D. aurita from the state of Minas Gerais, Brazil. This study indicates the existence of hemoplasma infections in D. aurita from the metropolitan region of Rio de Janeiro, and reinforce the need for new epidemiological inquiries to clarify the participation of these in the dynamics of circulation of tick-borne pathogens.
Detecção molecular de hemoplasmas em gambás-de-orelha-preta (Didelphis aurita Wied-Neuwied, 1826) resgatados do sudeste do Brasil, com evidência de um novo genótipo infectando marsupiais
Keywords: hemoplasmosis; Hemotropic Mycoplasma spp; opossums; wildlife